In-Situ Water Quality Improvement by Hypolimnion Oxygenation and Artificially Induced Mixing in a Drinking Water Reservoir - Zhou Zi-zhen, Huang Ting-lin, Gong Wei-jin, Li Yang, Liu Yue, Zhao Fu-wang, Bai Yang, Dou Yan-yan, Lv Jing-jing and Liu Hai-fang (Nature Environment and Pollution Technology, 2019)
Faced with the problems of hypolimnion dissolved oxygen (DO) depletion and water quality deterioration, a newly designed water quality improvement technology named water-lifting aerators (WLAs) was put into utilization to solve these problems in Jinpen Reservoir. During the hypolimnion oxygenation period, after 20 days operation of 8 WLAs with compressed air volume of 10 m3/h, the thickness of anaerobic layer was compressed from 17 m to 3.2 m. As for artificially induced mixing, after 18 days operation of 8 WLAs with compressed air volume of 50 m3/h (full capacity), the reservoir was mixed, and DO of the bottom water increased to more than 8 mg/L. Removal rates of TN, TP, NH4-N and TOC reached 25.5%, 50%, 29.8% and 19.4% respectively. Results of Biolog method showed that the activity of microbes and carbon source utilization were improved in the water of the controlled area compared with the uncontrolled area during the operation. WLAs have been proved to be an efficient technology in water quality improvement especially in hypolimnion oxygenation and artificially induced mixing.